A Critical Review on the Effectiveness of Using Various Play Methods to Enhance Cognitive Development in Early Childhood - Suhaini (Journal of Education, Teaching, and Learning, 2025)
This critical review examines the effectiveness of using various play methods to enhance cognitive development in early childhood. Employing a qualitative literature review approach, this study analyzes peer-reviewed research focused on children aged 2–6 years, selected through systematic checklists and sourced from academic databases such as Google Scholar, JSTOR, and ERIC. Thematic analysis was conducted to identify cognitive benefits associated with different types of play, including role-playing, puzzles, and educational technology. Findings indicate that structured play activities—such as number card games and logic puzzles—significantly support cognitive growth, particularly in numeracy and problem-solving, with some methods demonstrating up to 100% achievement in targeted learning outcomes. In contrast, less structured activities, such as Lego play, showed minimal impact on symbolic thinking among 4–5-year-old children. The review highlights that the effectiveness of play methods varies based on the nature of the activity and the child's developmental stage. These insights offer valuable implications for educators and curriculum developers in designing play-based strategies tailored to specific cognitive goals. Future studies are encouraged to investigate the long-term impact and cross-context adaptability of these play interventions in diverse early childhood education settings.